Graphis scripta / writing lichen. - BECHARD, DOMINIQUE (Malahat Review)
The article discusses two poetry collections: "Ox Lost, Snow Deep" by Burdick and "Graphis scripta / writing lichen" by Clare Goulet. Burdick's work presents a poetic persona grappling with systemic issues, including white supremacy and the impact of the coronavirus, while oscillating between humor and despair. In contrast, Goulet's collection offers a nuanced exploration of lichen, blending humor and natural observation, and is divided into three sections, with the first being particularly cohesive. The review highlights Goulet's commitment to understanding the non-human world through metaphor and language, ultimately celebrating the complexity of ecosystems and the interconnectedness of life.